2020
DOI: 10.1186/s40816-020-00219-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bioactive compounds by GC-MS and α-amylase and α-glucosidase inhibitory activity of Rauvolfia tetraphylla L. and Oroxylum indicum (L.) Kurz: an in vitro and in silico approach

Abstract: Background The practice of ethnomedicine remains to be the primary source of healthcare in many parts of the world, especially among the tribal communities. However, there is a lack of scientific outlook and investigation to authenticate and validate their medicinal values. Objective The present study investigated the trace and heavy metal content, bioactive compounds, α-amylase, and α-glucosidase inhibitory activity of Rauvolfia tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…α-Amylase and α-glucosidase are two crucial metabolic enzymes linked to diabetes. Several plants and plant-derived phytocompounds are reported to possess α-amylase and α-glucosidase inhibitory properties [31,32] . The present study revealed considerable inhibitory properties of the crude extract of L. crustacea against α-amylase and α-glucosidase enzymes in in vitro experiments.…”
Section: Resultsmentioning
confidence: 99%
“…α-Amylase and α-glucosidase are two crucial metabolic enzymes linked to diabetes. Several plants and plant-derived phytocompounds are reported to possess α-amylase and α-glucosidase inhibitory properties [31,32] . The present study revealed considerable inhibitory properties of the crude extract of L. crustacea against α-amylase and α-glucosidase enzymes in in vitro experiments.…”
Section: Resultsmentioning
confidence: 99%
“…All the optimized compounds were saved in the mol2 format to carry out the molecular docking studies with the enzymes αamylase, α-glucosidase, and human pancreatic lipase. Acarbose was used as the reference inhibitor for α-amylase and α-glucosidase enzymes (Swargiary and Daimari, 2020), while methoxy undecyl phosphonic acid (MUP) and orlistat were used as the reference inhibitors for the human pancreatic lipase enzyme (Trang et al, 2017).…”
Section: Molecular Docking-ligand Preparationmentioning
confidence: 99%
“…Crystal structures of α-amylase (PDB:2QV4), α-glucosidase (maltase) (PDB: 2QMJ), and human pancreatic lipase (PDB:1LPB) were downloaded from the PDB database (http://www.rcsb.org/pdb). These crystal structures are crystallized with the acarbose ligand used as a reference inhibitor for α-amylase and α-glucosidase, while the MUP and orlistat ligands were used for human pancreatic lipase (Trang et al, 2017;Swargiary and Daimari, 2020). The information of the amino acids of the active site in the enzymes was used as a reference to carry out a targeted coupling in the catalytic sites in each of the crystallized inhibitors.…”
Section: Molecular Docking-ligand Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Oroxylum indicum (L.) Kurz belongs to the family Bignoniaceae and is widely distributed throughout Asian counties, including Malaysia, Thailand, Indonesia, India, Vietnam, Philippines, China, Taiwan, and Japan. It is an important culinary herb with several medicinal and culinary purposes ( Swargiary and Daimari, 2020 ). The parts used in traditional medicinal practices are the fruit, seed, leaves, stems, bark and roots.…”
Section: Introductionmentioning
confidence: 99%